READING THE HISTORY OF ART THROUGH THE LINES OF DRAWING - Neris, Kleriston Luis Rocha (Seven Editora, 2026)
This research aims to present a methodological proposal that uses drawing as a teaching-learning tool in the teaching of Art History. Starting from the understanding of drawing as a visual language and pedagogical resource, the research seeks to enable meaningful learning of Art History content in high school, bridging theory and practice in the classroom. The proposal aims to break with the paradigm that high school is predominantly characterized by theoretical approaches, by encouraging practical activities that stimulate the active participation of students. In this sense, the practice of drawing is developed in an articulated way with historical and artistic content, through the creation of drawing groups, favoring observation and interpretation, and encompassing the different periods and styles of Art History selected by the teacher for the practices. The research is qualitative and uses the Arts-Based Research (ABR) methodology through the methods of Action Research and Participatory Research, where the first aims to solve practical problems with action (attitudes) and constant reflection, while the second aims at the emancipation and social transformation of the participants (researcher and researched). It is concluded that the use of drawing as a pedagogical methodology contributes to the development of aesthetic sensitivity, critical thinking, and student engagement in the learning process.DOI: https://doi.org/10.56238/sevened2026.008-001